PHYTOCHEMICAL CONTENT AND ANTIOXIDANT POTENTIAL OF DIFFERENT ORGANS OF EGGPLANT (SOLANUM MELONGENA L.) GROWN IN WEST JAVA-INDONESIA - Fidrianny, Irda; Winarsih, Siti; Ruslan, Komar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objectives: The goals of this research were to evaluate antioxidant potential from different organs of eggplant (Solanum melongena L.) using two antioxidant testing methods which were 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) and correlation of total phenolic and flavonoid content with their inhibitory concentration 50% (IC50) of DPPH, and exhibitory concentration 50% (EC50) of FRAP. Materials and Methods: Each sample was extracted by reflux using different polarity solvents. The extracts were evaporated using rotary evaporator. Antioxidant activities were tested using DPPH and FRAP assays, determination of total phenolic and flavonoid content were carried out by ultraviolet-visible spectrophotometry and correlation with their IC50 of DPPH and EC50 of FRAP capacities were analyzed by Pearson's method. Results: The lowest IC50 of DPPH scavenging activity 1.14 Î¼g/ml and the lowest EC50 of FRAP capacity 49.80 Î¼g/ml was given by ethanolic leaves extract of eggplant. Ethanolic leaves extract of eggplant also presented the highest total phenolic content (TPC) (8.87 g gallic acid equivalent/100 g), while the highest total flavonoid content was shown by ethyl acetate leaves extract (24.50 g quercetin equivalent/100 g). There was a significantly negative correlation between TPC in leaves and fruit extracts of eggplant with their IC50 of DPPH and EC50 of FRAP. Conclusions: All different extracts of eggplant organs (except n-hexane stem extract) were categorized as a very strong antioxidant by DPPH method. Phenolic compounds in eggplant leaves and fruit extracts were the major contributor in antioxidant activities by DPPH and FRAP methods. DPPH and FRAP showed linear results in antioxidant activities of eggplant leaves, fruit and stem extracts.